PERANCANGAN SISTEM MOBILE MONITORING BERBASIS ANDROID âSIMORIâ - Rahmantio, Ikhsan Dwi; Assadulloh, Muhammad Jundi; Dharmawan, Tubagus Rizky (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Monitoring is an activity to monitor or observe something. Many devices are mostly made in a static or stationary models, so that the monitoring process will be limited. We develop a device that can monitor with a higher mobility or switch positions according to the desired position. Therefore, as the rapid technological developments in the telecommunications sector, we create a monitoring system that has better mobility and user friendly. The control system of SIMORI is based on Android so many people can develop this device and make a better application in monitoring system.